An Empirical Investigation of Object-Oriented Query Writing for Three User Groups Using Casual Map - Chan, Lanie Y.W; Lee, Nung Kion; Shahren Ahmad, Zaidi Adruce (2009)
Understanding human's information processing for information retrieval task has contributed to the advancements of database modelling and user interaction design. In particular, the query writing model proposed by Ogden has improved our understanding on core steps in writing a relational database query. However, this model is limited in explaining query writing for more advance database models and the increased complexity of tasks we performed nowadays. It also failed to address the diverse needs of different user groups. In this study, we aims at a) identify extra elements in the traditional model for object-oriented query writing; b) construct, and compare and contrast the cognitive models of three user groups for database retrieval tasks; and c)analyze how the object-oriented database model has affect on the query writing task. This study expands on the existing cognitive model of query writing by seeking to identify pertinent exogenous elements to be used for modeling using causal maps. We employed the semi-structured interview methodology in the data collection and causal maps are constructed from the collected data. Several analyses were performed on the individual as well as merged collective causal maps to identify significant elements that are missing from the traditional query writing models. Results from the analyses revealed several new concepts for the three groups of users at different stages of query writing. We also report major observations on the novel elements in writing object-oriented query not available in traditional query models at discussion section. Our finding offer a better understanding on the inherent differences of query writing information processing for different user groups and insight over additional elements in cognitive model for object-oriented database model. This knowledge is also potential to improve the modern query graphical interface design as well as query writing training practice for object-oriented model databases.